Otak Bilingual: Sinergi Dwibahasa dalam Meningkatkan Fungsi Eksekutif - Anggraeni, Elisabeth Dwi; Sumardin, Selvi (Fakultas Psikologi Universitas Sanata Dharma, 2024)
Amidst the growing demand for proficiency in more than one language in today's global society, it is crucial to understand how bilingual abilities engage in various cognitive processes, particularly in executive functions from a neuropsychological perspective. The ability to acquire and use two languages affects high-level cognitive functions described through a tripartite model, including inhibitory control, working memory, and cognitive flexibility. Through a critical analysis of the literature, it is found that bilingual individuals often have an advantage in tasks requiring self-control and the management of complex information. This advantage is attributed to the need to manage and shift attention between two language systems, which intensively trains executive functions. This study also examines the neuropsychological implications of bilingual abilities, including structural and functional changes in the brain, particularly in the prefrontal cortex area. In conclusion, bilingualism not only affects linguistic abilities but also supports cognitive development. This research underscores the potential significance of bilingualism in education and personal development as a tool to enhance critical thinking skills and mental flexibility, which are valuable for learning and adapting to ever-changing environments.